Atlas of Minimally Invasive Surgery in Esophageal Carcinoma - Puntambekar, Shailesh; Cuesta, Miguel A.; SpringerLink (Online service) (London : Springer London, 2010)
Atlas of Minimally Invasive Surgery in Esophageal Carcinoma provides both an easy-to-follow procedural manual on the laparoscopic techniques for esophageal carcinoma and a comprehensive survey of the field of surgery on esophageal carcinoma. The following procedures are presented, using detailed anatomical photographs and step-by-step descriptions:Laparoscopic Trans-hiatal esophagectomy, Laparoscopic Trans-hiatal Resection for Distal and Gastro-Esophageal Junction Cancer: The Operative Technique, Trans-thoracic esophagectomy with 2 field nodal dissection, Trans-thoracic esophagectomy in the prone position. Throughout the book, the authors emphasise the similarities of the principles and steps between open and laparoscopic surgery, which significantly simplifies the conversion from one practice to the other. The accompanying films of these procedures on the Springer Extras website further enhances understanding of the surgical steps involved. This book also includes a description of anesthesia techniques, a guide to the use of staplers in laparoscopic surgery, a comparison of the energy sources available for laparoscopic surgery and a look forward to the increasing prevalence of robotic surgery for these procedures. A comprehensive and authoritative work on minimally invasive surgery in esophageal carcinoma, this book will prove essential reading for oncosurgeons, thoracoscopic surgeons and laparoscopic surgeons who will be performing these procedures.
Surgery for Cancer of the Esophagus (3z(BThe Continuing Evolution(3y (B-- Minimally Invasive Surgery in Esophageal Cancer: World Literature -- Staplers in Gastro-Esophageal Cancer Surgery -- Thoracoscopic and Laparoscopic Esophagectomy with Two-Field Nodal Clearance -- Laparoscopic Transhiatal Esophagectomy -- Thoracoscopic Esophageal Resection for Cancer in Prone Decubitus Position: Operative Technique -- Laparoscopic Transhiatal Resection for Distal and Gastro-Esophageal Junction Cancer: Operative Technique -- Robot-Assisted Thoracolaparoscopic Esophagectomy.s
Keywords: Medicine; Cancer -- Surgery; Surgery; Abdomen -- Surgery; Endoscopic surgery; Medicine & Public Health; Surgery; Surgical Oncology; Minimally Invasive Surgery; Abdominal Surgery